Preparation method of aqueous zinc ion battery electrolyte and battery

By using soluble potassium salts and zinc salts to prepare the electrolyte in aqueous zinc ion batteries, and adding electrolyte additives to form a protective layer, optimizing the positive and negative electrode materials and separators, the zinc negative electrode dendrites and corrosion problems are solved, and efficient battery performance and long life are achieved.

CN120432675APending Publication Date: 2025-08-05BENGBU COLLEGE +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510613643.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-13
Publication Date
2025-08-05

AI Technical Summary

Technical Problem

The zinc negative electrode is prone to form dendrites in aqueous zinc ion batteries, which lead to short circuit, corrosion and hydrogen evolution reactions, affecting the stability and life of the battery, and there are matching problems in the overall integration of the battery.

Method used

The electrolyte is prepared by soluble potassium and zinc salts, and the electrolyte additive is added to form a protective layer, the positive and negative electrode materials and separators are optimized, and the soft-packed battery is prepared through the slurry drawing process.

Benefits of technology

It improves the charging and discharging efficiency of zinc ion batteries, reduces dendrites, extends the battery cycle life, and ensures the stable operation of the battery under different working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120432675A_ABST
    Figure CN120432675A_ABST
Patent Text Reader

Abstract

The invention relates to an aqueous zinc ion battery electrolyte preparation method and a battery, the preparation method comprises the following steps: adding soluble sylvite into deionized water, stirring and dissolving, and then adding zinc salt to prepare a saturated zinc salt solution; and adding the solution of the electrolyte additive 1 and the solution of the electrolyte additive 2, and stirring for dissolving. The battery uses the prepared electrolyte, the positive electrode is a nickel hydroxide thick-film electrode plate, and the negative electrode is a zinc oxide thick-film electrode plate. The aqueous zinc ion battery electrolyte provided by the invention has relatively good cycle performance and capacity exertion when being used in a nickel-zinc battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing an aqueous zinc ion battery electrolyte and a battery, belonging to the technical field of new energy such as energy storage and communication batteries. Background Art

[0002] With technological advancements, the energy density and cycle life of aqueous zinc-ion batteries have improved. However, much research and exploration is still needed to optimize electrode materials.

[0003] Currently, zinc anodes still face some technical challenges. For example, dendrites easily form during charge and discharge, which can lead to short circuits and battery failure. Dendrite formation is related to the uneven electric field near the interface, which causes zinc to preferentially deposit at the tip.

[0004] Zinc negative electrodes are prone to corrosion and passivation in aqueous electrolytes. In most alkaline electrolytes, zinc negative electrodes will spontaneously corrode, while in neutral or acidic electrolytes there is relatively mild electrochemical corrosion, which will affect the stability and life of the battery.

[0005] The hydrogen evolution reaction will consume water in the electrolyte, affect zinc deposition and corrode the surface of the zinc negative electrode. The gas produced will even increase the internal pressure of the battery, causing battery expansion and electrolyte leakage, triggering safety problems.

[0006] There is still a need to continuously explore new electrolytes to solve existing problems.

[0007] Aqueous zinc-ion batteries require a well-matched and coordinated set of components (e.g., cathode, anode, electrolyte, separator, etc.) to achieve high performance and long battery life. However, there are still some challenges in overall battery integration, such as selecting the right material combination and optimizing the battery's structural design to ensure stable operation under different operating conditions. Summary of the Invention

[0008] In order to solve the above problems, the present invention discloses a method for preparing an aqueous zinc ion battery electrolyte and a battery, and its specific technical solutions are as follows:

[0009] A method for preparing an aqueous zinc ion battery electrolyte comprises the following steps:

[0010] Step 1: Add soluble potassium salt to deionized water and stir to dissolve to obtain potassium salt solution. The molar concentration of soluble potassium salt is 7-10 mol / L. Soluble potassium salt is the electrolyte in the electrolyte. After dissolving, potassium salt provides high mobility K + ions, enhance the ionic conductivity of the electrolyte, reduce the internal resistance of the battery, and thus improve the charge and discharge efficiency of the battery. +Ions regulate the deposition behavior on the zinc electrode surface and reduce the growth of zinc dendrites;

[0011] Step 2: Add zinc salt to the potassium salt solution obtained in step 1, heat it in a water bath to 50-90°C, stir it until it is saturated, and filter it to obtain a saturated zinc salt solution; the saturated zinc salt inhibits the dissolution of the zinc electrode and maintains the stability of the zinc electrode structure; the saturated zinc salt reacts through the equilibrium reaction Reduce the concentration of free zinc ions and slow down self-discharge;

[0012] Step 3: Add the electrolyte additive 1 solution to the saturated zinc salt solution obtained in step 2, and stir to dissolve;

[0013] The mass of the electrolyte additive 1 is 0.5% to 1% of the mass of the potassium salt, and the electrolyte additive 1 solution is a mixture of one or more of cetyltrimethylammonium bromide, tetraethylammonium bromide, polyethylene oxide and sodium dodecylsulfonate in any proportion;

[0014] In the zinc battery system, the electrolyte additive 1 forms a protective layer on the surface of the zinc negative electrode, inhibiting dendrite growth, side reactions and corrosion, and has the effects of electrostatic adsorption and interface modification on the zinc negative electrode;

[0015] Step 4: Add the electrolyte additive 2 solution to the solution obtained in step 3 and stir to dissolve;

[0016] The mass of the electrolyte additive 2 is 1% to 3% of the mass of the potassium salt. The electrolyte additive 2 solution is a mixture of one or more of lithium hydroxide, ethylene carbonate and triethyl phosphate in any proportion.

[0017] Furthermore, the soluble potassium salt in step 1 is a mixture of one or more of potassium hydroxide, potassium fluoride, and potassium carbonate in any proportion.

[0018] Furthermore, the soluble potassium salt in step 1 is a mixture of 8 mol / L potassium hydroxide and 2 mol / L potassium carbonate, or a mixture of 10 mol / L potassium hydroxide and 1 mol / L potassium fluoride, or 2 mol / L potassium hydroxide.

[0019] Furthermore, the zinc salt in step 2 is a mixture of one or more of zinc acetate, zinc sulfate and zinc oxide in any proportion.

[0020] Furthermore, the zinc salt in step 2 is a mixture of zinc oxide and zinc acetate, or a mixture of zinc oxide and zinc sulfate, or zinc oxide.

[0021] Furthermore, the electrolyte additive 1 is a mixture of sodium dodecyl sulfonate and cetyl trimethyl ammonium bromide, the mass of sodium dodecyl sulfonate and the mass of cetyl trimethyl ammonium bromide each account for 0.5% of the total mass of the electrolyte additive 1 solution, and the mass of the electrolyte additive 1 accounts for 1% of the mass of the potassium salt;

[0022] Alternatively, the electrolyte additive 1 is sodium dodecylsulfonate and tetraethylammonium bromide, the mass of sodium dodecylsulfonate and the mass of tetraethylammonium bromide each account for 0.5% of the total mass of the electrolyte additive 1 solution, and the mass of the electrolyte additive 1 accounts for 0.5% of the mass of the potassium salt;

[0023] Alternatively, the electrolyte additive 1 is composed of 0.1% tetraethylammonium bromide and 0.5% polyethylene oxide, the mass of tetraethylammonium bromide accounts for 0.1% of the total mass of the electrolyte additive 1 solution, the mass of polyethylene oxide accounts for 0.5% of the total mass of the electrolyte additive 1 solution, and the mass of the electrolyte additive 1 accounts for 0.5% of the mass of the potassium salt.

[0024] Furthermore, the electrolyte additive 2 is selected from lithium hydroxide and ethylene carbonate mixed in equal proportions;

[0025] Alternatively, the electrolyte additive 2 is selected from lithium hydroxide and triethyl phosphate, and the mass ratio of lithium hydroxide to triethyl phosphate is 2:1;

[0026] Alternatively, the electrolyte additive 2 is lithium hydroxide.

[0027] The present invention also claims protection for a battery, wherein the electrolyte of the battery is prepared by the above-mentioned method for preparing the electrolyte of the aqueous zinc ion battery;

[0028] The positive electrode of the battery is a nickel hydroxide thick film electrode, and the negative electrode is a zinc oxide thick film electrode, and the positive and negative electrodes are separated by a separator;

[0029] The battery is manufactured by adding a prepared electrolyte into a soft-pack battery consisting of a thick-film nickel hydroxide thick-film electrode pole piece and a thick-film zinc oxide thick-film electrode pole piece.

[0030] Furthermore, the specific preparation process of the thick-film nickel hydroxide thick-film electrode pole piece is as follows: take nickel hydroxide electrode material as 80% to 90% of the total mass, conductive agent as 5% to 10% of the total mass, PVA binder as 3% to 7% of the total mass, SBR binder as 2% to 3% of the total mass, prepare a slurry with a viscosity of 10000Pas by homogenization, and prepare the thick-film nickel hydroxide thick-film electrode pole piece / zinc oxide thick-film electrode pole piece by the process of slurry drawing + cutting + rolling.

[0031] Furthermore, the specific preparation process of the zinc oxide thick film electrode sheet is as follows: take 80% to 90% of the total mass of zinc oxide electrode material, 5% to 10% of the total mass of conductive agent, 3% to 7% of the total mass of CMC binder, and 2% to 3% of the total mass of SBR binder, and prepare a slurry with a viscosity of 10,000 Pas by homogenization, and prepare a thick film nickel hydroxide thick film electrode sheet / zinc oxide thick film electrode sheet by the process of slurry drawing + cutting + rolling.

[0032] The diaphragm is a composite diaphragm composed of filter paper and hydrophilic PP, and the pore size of the composite diaphragm is 5-15 μm.

[0033] The principle of the present invention is:

[0034] (1) One or more soluble potassium salts (potassium hydroxide, potassium fluoride, potassium carbonate) with a molar concentration of 7-10 mol / L are added to a certain amount of deionized water and stirred to dissolve; the potassium salt acts as an electrolyte in the electrolyte and is beneficial to maintaining the morphology of the negative electrode during the cycle.

[0035] Potassium salts dissolve to provide high mobility K + ions, enhance the ionic conductivity of the electrolyte, reduce the internal resistance of the battery, and thus improve the charge and discharge efficiency of the battery. + Ions regulate the deposition behavior on the zinc electrode surface, reducing the growth of zinc dendrites (which can pierce the separator and cause a short circuit), and extending the battery's cycle life. Potassium salts, as the foundation of the alkaline electrolyte, maintain a stable alkaline environment, ensuring the proper conduct of the nickel and zinc electrode reactions. In short, potassium salts as electrolytes help maintain the morphological stability of the negative electrode during cycling.

[0036] (2) Add one or more zinc salts (zinc acetate, zinc sulfate, zinc oxide) to the solution, heat it to 50-90°C in a water bath, stir it until saturated, and filter it.

[0037] Saturated zinc salts can inhibit the dissolution of zinc electrodes. Zinc electrodes are easily dissolved in alkaline electrolytes to form zincates (such as [Zn(OH)4] 2- ), resulting in changes in electrode shape and loss of active substances. The addition of saturated zinc salts inhibits excessive dissolution of zinc through the common ion effect, maintaining the stability of the electrode structure. At the same time, the dissolved zinc ions will deposit on the diaphragm or nickel electrode, causing self-discharge. Saturated zinc salts react through equilibrium Reduce the concentration of free zinc ions and slow down self-discharge. By controlling the dissolution-deposition balance of zinc, it can reduce electrode expansion or deformation and improve the cycle life of the battery.

[0038] Potassium salt and saturated zinc salt work synergistically to form a stable electrolyte system: the potassium salt + zinc salt system works synergistically, the potassium salt provides an alkaline conductive medium, and the zinc salt inhibits the side reaction of the zinc electrode. The two work together to optimize battery performance.

[0039] (3) One or more of the electrolyte additives 1 (hexadecyltrimethylammonium bromide, tetraethylammonium bromide, polyethylene oxide, sodium dodecylsulfonate) at 0.5% to 1% of the mass of the potassium salt is added to the solution and stirred to dissolve, thereby forming a protective layer on the surface of the zinc negative electrode to inhibit the corrosion of zinc and the growth of zinc negative electrode dendrites, thereby achieving a synergistic effect to slow down the corrosion of the zinc negative electrode and extend the life of the battery.

[0040] In the zinc battery system, electrolyte additive 1 (such as sodium dodecyl sulfate and hexadecyltrimethylammonium bromide) can effectively inhibit dendrite growth, side reactions and corrosion by forming a protective layer on the surface of the zinc negative electrode. Electrolyte additive 1 has the effect of electrostatic adsorption and interface modification on the zinc negative electrode. Hexadecyltrimethylammonium bromide (CTAB) and tetraethylammonium bromide (TEAB) are cationic surfactants. Their positively charged quaternary ammonium groups (such as -N + (CH3)3) will be adsorbed on the surface of the zinc negative electrode (negatively charged), and the hydrophobic long chains (such as hexadecyl) will be arranged outward to form a hydrophobic layer, blocking water molecules and free SO4 2- / OH - contact, inhibiting hydrogen evolution reaction (HER) and corrosion. 2+ flux, guiding Zn uniform deposition (suppressing dendrites). ZnO is generated in alkaline / neutral electrolytes due to local pH increases (Zn+2OH - →ZnO+H2O). The adsorption layer of CTAB / TEAB can reduce OH - Sodium dodecyl sulfate (SDS) is an anionic surfactant with film-forming effect. Its sulfonic acid group (-SO3 - ) will be with Zn 2+ Combined, an organic-inorganic hybrid protective layer (such as Zn(SO3R)2) is formed on the surface, which has ion selectivity and allows Zn 2+ It blocks H2O and O2. It inhibits the volume change during the dissolution / deposition of Zn. The hydrophobic chain of SDS can reduce water activity and reduce the generation rate of ZnO; at the same time, SO3- may bind to the ZnO surface to stabilize the interface. Polyimide (PAI) forms a flexible film through solution coating or in-situ polymerization in the electrolyte, physically isolating the zinc negative electrode from the electrolyte, inhibiting side reactions, and its high mechanical strength can inhibit dendrite puncture. The PAI film can cover the ZnO particles, preventing them from further reacting with the electrolyte and dissolving (ZnO+2H + →Zn 2++H2O). CTAB / SDS reduces the formation of ZnO by blocking OH- or H2O. It forms a composite layer with ZnO (such as ZnO-SO3R) to improve its electrochemical stability. PAI film can inhibit the dissolution-redeposition process of ZnO and avoid local Zn 2+ Uneven concentration.

[0041] (4) In order to form a protective layer on the surface of the current collector and slow down the corrosion of the current collector, one or more of the electrolyte additives 2 (lithium hydroxide, lithium sulfate, lithium carbonate, lithium phosphate, lithium silicate, ethylene carbonate, triethyl phosphate, etc.) with a molar concentration of 1% to 3% of the mass of the potassium salt is added to the solution and stirred to dissolve. Salts added to the solution can act as hydrolyzable anion additives. The electrolyte additive 2 and the HCO3 after hydrolysis in the solution prepared in steps 1-3 are - The combination of protons can catalyze the formation of a passivation layer on the surface of the current collector, thereby further inhibiting the corrosion of the current collector.

[0042] In nickel-zinc (Ni-Zn) batteries, the current collector is nickel foam. Electrolyte additive 2 (such as lithium hydroxide, ethylene carbonate, triethyl phosphate) can effectively slow down the corrosion of the current collector (such as the zinc negative electrode) by forming a protective layer on the current collector surface. The inorganic lithium salt additive (lithium hydroxide) in electrolyte additive 2 can adjust the pH in alkaline electrolytes, inhibiting the dissolution and dendrite growth of Zn. 2+ The reaction generates a Zn(OH)2 / Li2Zn(OH)4 passivation layer, which prevents further corrosion of Zn by the alkaline electrolyte.

[0043] The organic additives (ethylene carbonate EC, triethyl phosphate TEP) in electrolyte additive 2 are adsorbed on the Zn surface to form a hydrophobic layer, blocking H2O and OH - It can decompose to generate phosphorus-containing compounds (such as Li3PO4) to enhance the stability of the passivation layer. Electrolyte additives form a protective layer (such as ZnCO3, Zn3(PO4)2, organic polymers) to cover the surface of the current collector, physically isolate the electrolyte from Zn, and inhibit the formation of corrosive substances (OH - , H2O). The compounds generated by the reaction with the zinc negative electrode (such as Zn(OH)2 and ZnSiO3) have low solubility and preferentially exist stably in dynamic equilibrium, preventing the continuous dissolution of Zn. The organic additives in the electrolyte additive 2 (such as ethylene carbonate EC and triethyl phosphate TEP) can improve the oxidative stability of the electrolyte and inhibit the corrosion of the current collector under high voltage. The synergistic effect of the inorganic-organic composite layer forms a dense composite layer with both mechanical strength and ionic conductivity. During the charge and discharge process, some electrolyte additives 2 (such as Li3PO4) can dynamically repair the defects of the protective layer.

[0044] (5) The prepared electrolyte is added to a soft-pack battery composed of thick-film positive and negative electrode sheets (nickel hydroxide thick-film electrode sheets and zinc oxide thick-film electrode sheets) prepared by a slurry preparation process.

[0045] The beneficial effects of the present invention are:

[0046] Using the aqueous zinc ion battery electrolyte configured by the present invention, the nickel-zinc soft-pack battery has a first-cycle discharge capacity of 15 mAh at a 1C rate, and its capacity retention rate is 80% at the 1000th cycle. Therefore, the aqueous zinc ion battery electrolyte configured by the present invention has good cycle performance and capacity utilization when used in nickel-zinc batteries, thereby providing a reference basis for the large-scale application of aqueous zinc ion energy storage batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is a cycle performance diagram of the aqueous zinc ion battery of the present invention. DETAILED DESCRIPTION

[0048] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0049] Three specific embodiments of the present invention are given below:

[0050] Example 1

[0051] Step (1) adding potassium hydroxide and potassium carbonate with a molar concentration of 8 mol / L and stirring to dissolve in a certain amount of deionized water to obtain a potassium salt solution.

[0052] Step (2) adding zinc oxide + zinc acetate to the potassium salt solution obtained in step (1), heating to 90° C. in a water bath, stirring until saturated, and filtering by suction to obtain a saturated zinc oxide solution.

[0053] Step (3) Adding 1% of potassium salt as electrolyte additive 1 (0.5% of sodium dodecylsulfonate + 0.5% of hexadecyltrimethylammonium bromide) to the saturated zinc oxide solution obtained in step (2) and stirring to dissolve.

[0054] Step (4) adding 1% by mass of potassium salt of electrolyte additive 2: 0.5% of lithium hydroxide and 0.5% of ethylene carbonate to the solution obtained in step (3) and stirring to dissolve.

[0055] Step (5) The specific preparation process of the positive and negative electrodes is as follows: nickel hydroxide / zinc oxide electrode material accounts for 90% of the total mass, conductive agent accounts for 5% of the total mass, PVA binder / CMC binder accounts for 3% of the total mass, and SBR binder accounts for 2% of the total mass. A slurry with a viscosity of 10,000 Pas is prepared by homogenization, and thick-film electrode plates are prepared by slurry drawing, cutting, and rolling. The positive electrode is a nickel hydroxide thick-film electrode plate, and the negative electrode is a zinc oxide thick-film electrode plate.

[0056] Step (6) adding the electrolyte prepared in steps (1) to (4) into a soft-pack battery composed of thick-film positive and negative electrode sheets (nickel hydroxide thick-film electrode sheets and zinc oxide thick-film electrode sheets) prepared by a slurry preparation process to prepare an aqueous zinc ion battery soft-pack battery.

[0057] Example 2

[0058] Step (1) adding potassium hydroxide with a molar concentration of 10 mol / L and potassium fluoride with a molar concentration of 1 mol / L into a certain amount of deionized water and stirring to dissolve the mixture to obtain a potassium salt solution.

[0059] Step (2) adding zinc oxide + zinc sulfate to the potassium salt solution obtained in step (1), heating to 70° C. in a water bath, stirring until saturated, and filtering by suction to obtain a saturated zinc oxide solution.

[0060] Step (3) Adding 0.5% of potassium salt to the saturated zinc oxide solution obtained in step (2) is an electrolyte additive 1 (0.5% sodium dodecylsulfonate + 0.5% tetraethylammonium bromide (TEAB)) and stirring to dissolve.

[0061] Step (4) Add 3% of potassium salt by mass of electrolyte additive 2:2% of lithium hydroxide and 1% of triethyl phosphate into the solution and stir to dissolve.

[0062] The specific preparation process of the positive and negative electrodes in step (5) is as follows: nickel hydroxide (or zinc oxide) electrode material is 80% of the total mass, the conductive agent is 10% of the total mass, the PVA binder / CMC binder) is 7% of the total mass, and the SBR binder is 3% of the total mass. A slurry with a viscosity of 10000 Pas is prepared by homogenization, and a thick film electrode pole piece is prepared by slurry drawing + cutting + rolling.

[0063] Step (6) adding the electrolyte prepared in steps (1) to (4) into a soft-pack battery composed of thick-film positive and negative electrode sheets (nickel hydroxide thick-film electrode sheets and zinc oxide thick-film electrode sheets) prepared by a slurry preparation process to prepare an aqueous zinc ion battery soft-pack battery.

[0064] Example 3

[0065] Step (1) adding potassium hydroxide with a molar concentration of 2 mol / L into a certain amount of deionized water and stirring to dissolve the mixture to obtain a potassium salt solution.

[0066] Step (2) adding zinc oxide to the potassium salt solution obtained in step (1), heating to 90° C. in a water bath, stirring until saturated, and filtering by suction to obtain a saturated zinc oxide solution.

[0067] Step (3) Add electrolyte additive 1 (0.1% tetraethylammonium bromide + 0.5% polyethylene oxide) with a potassium salt mass of 0.5% to the saturated zinc oxide solution obtained in step (2) and stir to dissolve.

[0068] Step (4) adding electrolyte additive 2: lithium hydroxide with a mass percentage of 1.5% of potassium salt into the solution and stirring to dissolve.

[0069] Step (5) The specific preparation process of thick film positive and negative electrodes is as follows: take nickel hydroxide (or zinc oxide) electrode material as 85% of the total mass, take conductive agent as 8% of the total mass, PVA binder / CMC binder as 5% of the total mass, SBR binder as 2% of the total mass, prepare a slurry with a viscosity of 10000Pas by homogenization, and prepare thick film electrode pole pieces by slurry drawing + cutting + rolling.

[0070] Step (6) adding the electrolyte prepared in steps (1) to (4) into a soft-pack battery composed of thick-film positive and negative electrode sheets (nickel hydroxide thick-film electrode sheets and zinc oxide thick-film electrode sheets) prepared by a slurry preparation process to prepare an aqueous zinc ion battery soft-pack battery.

[0071] The battery prepared in Example 1 was tested. Using the configured electrolyte, the nickel-zinc soft-pack battery achieved a first-cycle discharge capacity of 14.1 mAh at a 1C rate, and a capacity retention rate of 97.1% at the 410th cycle. Therefore, the aqueous zinc-ion battery electrolyte configured in the present invention exhibits good cycling performance and capacity utilization in nickel-zinc batteries, providing a reference for the large-scale application of aqueous zinc-ion energy storage batteries. The cycling performance of the aqueous zinc-ion battery is shown in Figure 1.

[0072] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs. It should also be understood that terms such as those defined in common dictionaries should be understood to have meanings consistent with their meanings in the context of the prior art and, unless defined as such herein, will not be interpreted in an idealized or overly formal sense.

[0073] With the above-described preferred embodiments of the present invention as a guide, and with reference to the above description, relevant personnel are fully capable of making various changes and modifications without departing from the technical scope of this invention. The technical scope of this invention is not limited to the contents of the specification and must be determined according to the scope of the claims.

Claims

1. A method for preparing an aqueous zinc ion battery electrolyte, characterized in that: The steps are as follows: Step 1: Add a soluble potassium salt to deionized water and stir to dissolve it to obtain a potassium salt solution. The molar concentration of the soluble potassium salt is 7-10 mol / L. The soluble potassium salt is an electrolyte in the electrolyte. After the potassium salt is dissolved, it provides K+ ions with high mobility, enhances the ionic conductivity of the electrolyte, reduces the internal resistance of the battery, and thus improves the charge and discharge efficiency of the battery. At the same time, the K+ ions regulate the deposition behavior of the zinc electrode surface and reduce the growth of zinc dendrites. Step 2: Add zinc salt to the potassium salt solution obtained in step 1, heat it in a water bath to 50-90°C, stir it until it is saturated, and filter it to obtain a saturated zinc salt solution; the saturated zinc salt inhibits the dissolution of the zinc electrode and maintains the stability of the zinc electrode structure; the saturated zinc salt reacts through the equilibrium reaction Reduce the concentration of free zinc ions and slow down self-discharge; Step 3: Add the electrolyte additive 1 solution to the saturated zinc salt solution obtained in step 2, and stir to dissolve; The mass of the electrolyte additive 1 is 0.5% to 1% of the mass of the potassium salt, and the electrolyte additive 1 solution is a mixture of one or more of cetyltrimethylammonium bromide, tetraethylammonium bromide, polyethylene oxide and sodium dodecylsulfonate in any proportion; In the zinc battery system, the electrolyte additive 1 forms a protective layer on the surface of the zinc negative electrode, inhibiting dendrite growth, side reactions and corrosion, and has the effects of electrostatic adsorption and interface modification on the zinc negative electrode; Step 4: Add the electrolyte additive 2 solution to the solution obtained in step 3 and stir to dissolve; The mass of the electrolyte additive 2 is 1% to 3% of the mass of the potassium salt. The electrolyte additive 2 solution is a mixture of one or more of lithium hydroxide, ethylene carbonate and triethyl phosphate in any proportion.

2. The method for preparing an aqueous zinc ion battery electrolyte according to claim 1, wherein The soluble potassium salt in step 1 is a mixture of one or more of potassium hydroxide, potassium fluoride and potassium carbonate in any proportion.

3. The method for preparing an aqueous zinc ion battery electrolyte according to claim 2, wherein The soluble potassium salt in step 1 is a mixture of 8 mol / L potassium hydroxide and 2 mol / L potassium carbonate, or a mixture of 10 mol / L potassium hydroxide and 1 mol / L potassium fluoride, or 2 mol / L potassium hydroxide.

4. The method for preparing an aqueous zinc ion battery electrolyte according to claim 1, wherein The zinc salt in step 2 is a mixture of one or more of zinc acetate, zinc sulfate and zinc oxide in any proportion.

5. The method for preparing an aqueous zinc ion battery electrolyte according to claim 4, wherein The zinc salt in step 2 is a mixture of zinc oxide and zinc acetate, or a mixture of zinc oxide and zinc sulfate, or zinc oxide.

6. The method for preparing an aqueous zinc ion battery electrolyte according to claim 1, wherein The electrolyte additive 1 is a mixture of sodium dodecylsulfonate and cetyltrimethylammonium bromide, the mass of sodium dodecylsulfonate and the mass of cetyltrimethylammonium bromide respectively account for 0.5% of the total mass of the electrolyte additive 1 solution, and the mass of the electrolyte additive 1 accounts for 1% of the mass of the potassium salt; Alternatively, the electrolyte additive 1 is sodium dodecylsulfonate and tetraethylammonium bromide, the mass of sodium dodecylsulfonate and the mass of tetraethylammonium bromide each account for 0.5% of the total mass of the electrolyte additive 1 solution, and the mass of the electrolyte additive 1 accounts for 0.5% of the mass of the potassium salt; Alternatively, the electrolyte additive 1 is composed of 0.1% tetraethylammonium bromide and 0.5% polyethylene oxide, the mass of tetraethylammonium bromide accounts for 0.1% of the total mass of the electrolyte additive 1 solution, the mass of polyethylene oxide accounts for 0.5% of the total mass of the electrolyte additive 1 solution, and the mass of the electrolyte additive 1 accounts for 0.5% of the mass of the potassium salt.

7. The method for preparing an aqueous zinc ion battery electrolyte according to claim 1, wherein The electrolyte additive 2 is a mixture of lithium hydroxide and ethylene carbonate in equal proportions; Alternatively, the electrolyte additive 2 is selected from lithium hydroxide and triethyl phosphate, and the mass ratio of lithium hydroxide to triethyl phosphate is 2:1; Alternatively, the electrolyte additive 2 is lithium hydroxide.

8. A battery, characterized in that: The electrolyte of the battery is prepared by the method for preparing an aqueous zinc ion battery electrolyte according to any one of claims 1 to 5; The positive electrode of the battery is a nickel hydroxide thick film electrode, and the negative electrode is a zinc oxide thick film electrode, and the positive and negative electrodes are separated by a separator; The battery is manufactured by adding a prepared electrolyte into a soft-pack battery consisting of a thick-film nickel hydroxide thick-film electrode pole piece and a thick-film zinc oxide thick-film electrode pole piece.

9. The battery according to claim 8, characterized in that The specific preparation process of the thick-film nickel hydroxide thick-film electrode pole piece is as follows: take nickel hydroxide electrode material as 80% to 90% of the total mass, conductive agent as 5% to 10% of the total mass, PVA binder as 3% to 7% of the total mass, SBR binder as 2% to 3% of the total mass, prepare a slurry with a viscosity of 10000Pas by homogenization, and prepare the thick-film nickel hydroxide thick-film electrode pole piece / zinc oxide thick-film electrode pole piece by the process of slurry drawing + cutting + rolling.

10. The battery according to claim 8, characterized in that The specific preparation process of the zinc oxide thick film electrode sheet is as follows: take 80% to 90% of the total mass of zinc oxide electrode material, 5% to 10% of the total mass of conductive agent, 3% to 7% of the total mass of CMC binder, and 2% to 3% of the total mass of SBR binder, and prepare a slurry with a viscosity of 10000Pas by homogenization, and prepare a thick film nickel hydroxide thick film electrode sheet / zinc oxide thick film electrode sheet by the process of slurry drawing + cutting + rolling.

Citation Information

Cited By

  • Aqueous zinc ion battery electrolyte and preparation and application thereof

    CN121282388A